2020
DOI: 10.1085/jgp.201912523
|View full text |Cite
|
Sign up to set email alerts
|

Differentially poised vesicles underlie fast and slow components of release at single synapses

Abstract: In several types of central mammalian synapses, sustained presynaptic stimulation leads to a sequence of two components of synaptic vesicle release, reflecting the consecutive contributions of a fast-releasing pool (FRP) and of a slow-releasing pool (SRP). Previous work has shown that following common depletion by a strong stimulation, FRP and SRP recover with different kinetics. However, it has remained unclear whether any manipulation could lead to a selective enhancement of either FRP or SRP. To address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Sakaba and Neher, 2001). However, recent studies indicate very fast vesicle recruitment steps (Blanchard et al, 2020;Chang et al, 2018;Doussau et al, 2017;Hallermann et al, 2010;Lee et al, 2012;Malagon et al, 2020;Miki et al, 2016;Miki et al, 2018;Saviane and Silver, 2006;Valera et al, 2012). These findings further complicate the dissection between fusion, priming, and recruitment steps.…”
Section: Ca 2+ -Sensitivity Of Vesicle Recruitmentmentioning
confidence: 99%
“…Sakaba and Neher, 2001). However, recent studies indicate very fast vesicle recruitment steps (Blanchard et al, 2020;Chang et al, 2018;Doussau et al, 2017;Hallermann et al, 2010;Lee et al, 2012;Malagon et al, 2020;Miki et al, 2016;Miki et al, 2018;Saviane and Silver, 2006;Valera et al, 2012). These findings further complicate the dissection between fusion, priming, and recruitment steps.…”
Section: Ca 2+ -Sensitivity Of Vesicle Recruitmentmentioning
confidence: 99%
“…In particular, it remains unclear whether the SRP, the primed FRP, and the superprimed FRP release their SVs according to a parallel scheme, to a sequential scheme, or to a mixed parallel-sequential scheme ( 5 , 8 , 12 , 20 25 ), even though recent studies often favor sequential schemes ( 9 , 26 , 27 ). In certain additional synapses [cerebellar parallel fiber to molecular layer interneuron ( 28 , 29 ), molecular layer interneuron to molecular layer interneuron ( 30 ), and hippocampal mossy fiber to interneuron ( 31 )], studies carried out at the level of individual AZs (“simple synapse recording”: ref. 32 ) suggest a sequential binding of incoming SVs to a “replacement site” and an associated “docking site” before release.…”
mentioning
confidence: 99%
“…This is different from what was found by Bouhours et al, who showed that the analog-digital coupling was dependent on the activation of PKC. In a recent work, Blanchard et al 25 showed that the modulation of basal calcium with local calcium photolysis in a single MLI axonal varicosity can increase release through a modulation of the docking site occupancy. In the present work, both the amplitude and the half-width of the axAP seem to be very resistant to various manipulations, like an increase in the stimulation frequency ( supplementary figure 4 ) and somatic depolarization ( Figure 4 ), which is in agreement with what has been described by Alle and Geiger (see above) and by Ritzau-Jost et al 26 , who showed that in neocortical (L5) fast-spiking GABAergic cells the width of the axAP does not change when the stimulation frequency increases.…”
Section: Discussionmentioning
confidence: 99%